One size fits all? Annäherungen an Leitlinien zum Transfer in Rahmen von Innovationsprogrammen - Daniel-Söltenfuß, Desiree; Kremer, H.-Hugo; Kückmann, Marie-Ann (Berufsbildungsforschung. Rezeption - Translation - Transfer)

Blockchain-based reputation systems for business-to-business services: designing a reputation mechanism to reduce information asymmetry in professional consulting - Hemmrich, Simon; Nissen, Volker; Beverugen, Daniel; Pauls, Josias Daniel Miño (Information Systems and e-Business Management)
Reputation systems to rate companies’ performances remain largely unexplored in research and are scarcely used in business-to-business (B2B) practice. Such systems are essential for businesses seeking trustworthy partners, as they help reduce information asymmetry, lower buyers' transaction risks, and allow high-quality service providers to justify premium pricing. Unlike traditional review-based systems in the business-to-consumer (B2C) context, we propose a B2B reputation mechanism in which buyers commit to a rating payment before a transaction. Once the buyer finalizes the rating, this payment is executed and recorded on a blockchain as an immutable, secure ledger. Our system mimics natural trust-building mechanisms with ratings that are (1) monetary-based, (2) stake-based, (3) non-aggregated, (4) involve counter-ratings, (5) selectively sellable, (6) individually comparable, (7) stored on a blockchain, (8) and monitored by a third instance. This system provides a novel approach to fostering trust in B2B transactions by reducing information asymmetry and transaction risk. We illustrate the mechanism’s application in the consulting sector. Our analysis has identified 23 institutional trust and distrust dimensions that promote establishing institutional trust through the proposed mechanism. Qualitative interviews suggest that, while complex and challenging to apply, this mechanism can foster trust in B2B transactions. Given the low maturity in the application domain—rating professional business services with business reputation systems—and solution domain—using monetary stakes for ratings, this system stands as a potential invention.

Künstlerische Zusammenarbeit zwischen Ehekonvention und Sublimation. Hans Werner Henzes Bühnenschaffen mit Ingeborg Bachmann, W.H. Auden und Chester Kallman - Tumat, Antje ((Wahl-)Verwandtschaften.Gemeinschaftliches kulturelles Handeln)
A preference for music theatre works is characteristic of Hans Werner Henze's oeuvre, as is his close collaboration with famous 20th-century authors, who wrote the libretti for his music theatre works. This paper explores the artistic collaborations of Hans Werner Henze and Ingeborg Bachmann on the one hand and Henze, Chester Kallman and W.H. Auden on the other in the context of their joint operatic work, surviving correspondence and poetological essays. This is set against the backdrop of how personal relationships can influence collaboration in the performing arts. In both cases, the letters and biographical writings of the aforementioned working groups, read from a gender perspective and with regard to creativity, forms of relationship and artistic collaboration, point to a tension between potential and desired personal relationships, the confrontation with marriage as a conventional social framework and artistic collaboration as a long-term connection.

Speech Synthesis along Perceptual Voice Quality Dimensions - Rautenberg, Frederik; Kuhlmann, Michael; Seebauer, Fritz; Wiechmann, Jana; Wagner, Petra; Haeb-Umbach, Reinhold (ICASSP 2025 - 2025 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

G.E. Lessings 'Hamburgische Dramaturgie': Zwischen ästhetischer Theorie und dramatischer Praxis - Steigerwald, Jörn (G.E. Lessings 'Hamburgische Dramaturgie': Zwischen ästhetischer Theorie und dramatischer Praxis)

Erbstreitigkeiten: Lessing, Voltaire und der französische Klassizismus - Steigerwald, Jörn (G.E. Lessings 'Hamburgische Dramaturgie': Zwischen ästhetischer Theorie und dramatischer Praxis)

'Wunderbare' Schau-Spiele. Zu Carlo Gozzis 'Turandot' - Steigerwald, Jörn (Artes. Zeitschrift für Literatur und die Künste der frühmodernen Welt)

G.E. Lessings 'Hamburgische Dramaturgie': Zwischen ästhetischer Theorie und dramatischer Praxis

Enhancing mechanical strength of Ti-6Al-4V sheet material by short-time sub-β-transus solution heat treatment and additional short-time annealing - Pfeffer, Nina; Jäger, Stefanie Nicole; Kaiser, Maximilian Alexander; Meyer, Thomas; Stark, Andreas; Höppel, Heinz Werner (Materials Science and Engineering: A)

Interacting with fallible AI: Is distrust helpful when receiving AI misclassifications? - Peters, Tobias Martin; Scharlau, Ingrid (Frontiers in Psychology)
Due to the application of Artificial Intelligence (AI) in high-risk domains like law or medicine, trustworthy AI and trust in AI are of increasing scientific and public relevance. A typical conception, for example in the context of medical diagnosis, is that a knowledgeable user receives AIgenerated classification as advice. Research to improve such interactions often aims to foster the user’s trust, which in turn should improve the combined human-AI performance. Given that AI models can err, we argue that the possibility to critically review, thus to distrust, an AI decision is an equally interesting target of research. We created two image classification scenarios in which the participants received mock-up AI advice. The quality of the advice decreases for a phase of the experiment. We studied the task performance, trust and distrust of the participants, and tested whether an instruction to remain skeptical and review each piece of advice led to a better performance compared to a neutral condition. Our results indicate that this instruction does not improve but rather worsens the participants’ performance. Repeated single-item self-report of trust and distrust shows an increase in trust and a decrease in distrust after the drop in the AI’s classification quality, with no difference between the two instructions. Furthermore, via a Bayesian Signal Detection Theory analysis, we provide a procedure to assess appropriate reliance in detail, by quantifying whether the problems of under- and over-reliance have been mitigated. We discuss implications of our results for the usage of disclaimers before interacting with AI, as prominently used in current LLM-based chatbots, and for trust and distrust research.
Keywords: trust in AI; trust; distrust; human-AI interaction; Signal Detection Theory; Bayesian parameter estimation; image classification

On the Dynamical Hierarchy in Gathering Protocols with Circulant Topologies - Gerlach, Raphael; von der Gracht, Sören; Dellnitz, Michael (Lecture Notes in Computer Science)

Increasing the sensitivity of ultrasonic transmission measurements for elastic material parameter estimation - Dreiling, Dmitrij; Itner, Dominik; Gravenkamp, Hauke; Claes, Leander; Birk, Carolin; Henning, Bernd (Measurement Science and Technology)
Abstract Ultrasonic transmission measurements can be used for material characterization, as the propagation time of sound waves and thus their velocity depends on the elastic material parameters. Measurement results for the elastic material parameters are acquired non-destructively using ultrasonic transmission measurements of hollow cylindrical polymer specimens. To determine the material parameters, an inverse approach is used comparing measurements with simulated data. Previous studies show that the procedure exhibits low sensitivity with respect to the shear parameters of the material. In order to increase the sensitivity, we propose to apply a spatially annular excitation on the base of the specimen. As a measure to analyse the sensitivities with respect to all parameters and their linear independence, we observe the volume of the parallelotope of the sensitivity vectors. Here, a scaled boundary finite element formulation of wave propagation in the specimen is expanded to yield derivative information directly, and a sensitivity analysis can be carried out efficiently. Finally, the results of this sensitivity analysis with regard to the annular excitation are also applied to the measurement setup.
Keywords: Sensitivity analysis; Ultrasonic transducer; Guided waves; Polymers; Gram determinant

Emotions in mathematics learning: a systematic review and meta-analysis - Schönherr, Johanna; Schukajlow, Stanislaw; Pekrun, Reinhard (ZDM – Mathematics Education)
Abstract Academic emotions play a crucial role in mathematics learning, significantly influencing motivation, academic achievement, and career aspirations in mathematics. With the notable increase in research on emotions in recent years, our review uses Pekrun’s control-value theory with two primary objectives: to systematically describe the characteristics of emotions in recent research through a systematic review, and to synthesize evidence on the relationships between specific emotions, control-value antecedents, and mathematics achievement via a meta-analysis. The systematic review of 112 studies revealed that more than 100 specific emotions have been addressed in recent research, which we analyzed based on key emotion characteristics: valence and activation, type of object, temporal stability, and social context. The findings from the systematic review provide an overview of mathematics-specific objects that emotions have referred to in the most recent research. The subsequent meta-analysis demonstrated that mathematics achievement (e.g., test scores and grades) was positively related to enjoyment, hope, and pride ( $$\overline{r}$$ r ¯ = .247, .224, and .344, respectively) but negatively related to anger, boredom, frustration, hopelessness, and shame ( $$\overline{r}$$ r ¯ = − .322, − .187, − .207, − .378, and − .291, respectively). Theoretical and practical implications of these results are discussed.

Maximizing the benefits of student-generated drawing for real-world problem solving - Schönherr, Johanna; Mayer, Richard E. (Contemporary Educational Psychology)

Zeitfestigkeit von infrarotgeschweißten gefüllten Polyamiden - Gevers, Karina
Keywords: Infrarotschweißen; Zeitfestigkeit; Polyamide

Becker, Matthias: Ehe, Familie und Agamie Die Begründung von Lebensformen angesichts gesellschaftlicher Pluralität im Neuen Testament und heute - Breuer, Saskia Rebecca (ThRv)

Der erste transhumane Albtraum. Wissenschaftsethik in Mary Shelleys Frankenstein, 1818 - Vukadinovic, Vojin Sasa (Von Transzendenz zum Transhumanismus. Deutungskulturen von (Un)Heilsgeschichte im 19. und 20. Jahrhundert)

Schattenprinzip und Klimawandel - Entwicklungschancen für Lehrende und Lernende im Kontext des ökologischen Lernens - Garske, Volker (Wissenschaft aus Leidenschaft. Persönliche, biografische, wissenschaftliche Aspekte. FS Cyprian Rogowski zum 70. Geburtstag)

„… und voll wurde die Erde von ḥāmās“ (Gen 6,11) – Biblische Schöpfungserzählungen im Kontext von Krieg und Gewalt - Garske, Volker

Die Bergpredigt (Mt 5,1-7,29). Interpretationen - Unterrichtsmodell